DIDACTIC ASPECTS OF TEACHING ACCOUNTING IN HIGHER SCHOOL - E. Y. Voronova (Vestnik MGIMO-Universiteta)
The article considers didactic aspects of competence-based and interdisciplinary approaches to teaching accounting for university students. The author proves the necessity to improve the national accounting education aimed at cohesion of theory and practice, production of new knowledge, its spread and usage via innovation activities. The article criticizes traditional approach to typical problem-solving connected with calculations and memorizing double-entries for failing to develop student’s analytical skills. It also promotes case-studies to infuse knowledge and skills enabling students to professionally solve real life like problems which they are likely to face. The article also considers seminars in the light of communication and its frame to inform students of innovation theoretical concepts of accounting. In addition the author looks into changes in the role of the lecture teaching accounting as well as forms and methods of teaching accounting as well as forms and methods of teaching accounting due to access to IT. The article underlines the importance of increased autonomy and self-reliance of students. It also describes professional literature as a key information resource in accounting.